2020
DOI: 10.1136/bmjgast-2020-000462
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and risk factors for ERCP-related complications in a predominantly black urban population

Abstract: ObjectiveThere is a lack of literature on postendoscopic retrograde cholangiopancreatography (ERCP) complications in predominantly black urban populations of low socioeconomic status. The aim of this study was to determine the incidence and predictors of post-ERCP complications in this patient population.DesignRetrospective review of ERCP cases performed at two hospitals from 2007 to 2017 was performed. The categories of complications evaluated were overall complications, severe or fatal complications, pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
2
0
3
Order By: Relevance
“…Overall, this study demonstrated that severe adverse events related to pediatric ERCPs were uncommon, with overall rates of adverse events occurring in 9.7% of cases, which is similar to that of other retrospective adult and pediatric studies (27,32–34). Adverse events in this study included PEP, non‐PEP pain, bleeding, fever of unknown etiology, cholangitis, and perforation.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, this study demonstrated that severe adverse events related to pediatric ERCPs were uncommon, with overall rates of adverse events occurring in 9.7% of cases, which is similar to that of other retrospective adult and pediatric studies (27,32–34). Adverse events in this study included PEP, non‐PEP pain, bleeding, fever of unknown etiology, cholangitis, and perforation.…”
Section: Discussionsupporting
confidence: 86%
“…İnvaziv bir girişim olması nedeniyle literatürde %10'lara ulaşan ERCP ilişkili komplikasyonlar bildirilmiştir (4,5). ERCP'nin en sık görülen komplikasyonları pankreatit, kanama, kolanjit, kolesistit ve perforasyondur (4,5). ERCP ile ilişkili komplikasyonları azaltmak için risk faktörlerinin çok iyi bilinmesi ve uygun endikasyonlarda ERCP yapılması önerilmektedir (5).…”
Section: Bulgularunclassified
“…Indications, results, and complications of endoscopic retrograde cholangiopancreatography: 3-year data of a third-level center in the Eastern Black Sea Region İD Sami FİDAN, İD Arif Mansur COŞAR Karadeniz Teknik Üniversitesi, Tıp Fakültesi, Gastroenteroloji Bilim Dalı, Trabzon yı 2-3 gün plansız hastanede yatması hafif, dört ila 10 gün yatması orta, 10 günden fazla yatması, cerrahi ya da invaziv radyolojik müdahale gereksinimi veya ölümle sonuçlanan komplikasyonlar ise ciddi komplikasyon olarak tanımlandı (4,5). ERCP ilişkili pankreatitin tanısı; uyumlu klinik ve/veya radyolojik bulguların varlığı ile birlikte serum amilaz düzeylerinin normal üst sınırın üç katından daha yüksek olması ile konuldu (5,13).…”
Section: Endoskopik Retrograd Kolanjiyopankreatografinin Endikasyonları Sonuçları Ve Komplikasyonları: Doğu Karadeniz'deki üçüNcü Basamakunclassified
“…La CPRE, que se ha transformado de ser principalmente diagnóstica a una función fundamentalmente terapéutica (Johnson et al, 2020), es de uso diverso, asociándose sobre todo con trastornos pancreatobiliares. Este procedimiento fue inicialmente introducido en 1968 por McCune (Kwak et al, 2020).…”
Section: Introductionunclassified